BOLALARDA METABOLIK SINDROM VA SEMIZLIK (METABOLIC SYNDROME IN CHILDREN) - Musakova Shaxnozaxon Ulug'bek qizi,; Qobiljonova Sarvinoz Raxmatullo qizi, (TADQIQOTLAR, 2026)
Annotation Metabolic syndrome in children represents a serious and increasing global health problem  closely  associated  with  the  rising  prevalence  of  childhood  obesity.  This syndrome  is  defined  by  a  combination  of  metabolic  disorders,  including  insulin resistance,  abdominal  obesity,  dyslipidemia,  and  elevated  blood  pressure,  which significantly increase the risk of type 2 diabetes mellitus and cardiovascular diseases in  later  life.  Evidence  suggests  that  unhealthy  dietary  habits,  insufficient  physical activity,  genetic  factors,  and  environmental  influences  play  a  critical  role  in  the development of metabolic syndrome during childhood [1, 2]. Early identification and preventive strategies, such as lifestyle modification and nutritional interventions, are essential  to  reduce  long-term  metabolic  and  cardiovascular  complications  and  to improve overall pediatric health outcomes [3, 4].